2013
DOI: 10.1097/nmd.0b013e318288e298
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Marital Adjustment in Remitted Psychiatric Illness

Abstract: People with mental disorders experience impaired quality of life (QOL). In India, spouses form the most important caregiver for the patient and therefore impact the patients' QOL. However, relatively little is known about marital adjustment, which can definitely influence QOL of patients with mental illness. This study intended to explore marital adjustment and QOL among remitted patients with schizophrenia (SC), depression, and bipolar disorders (BPADs) and to study differences, if any, between the groups. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
(31 reference statements)
0
15
1
2
Order By: Relevance
“…In this study the marital status is also not showing any significant relation as they also found to be somewhat equal in numbers with more for the married individuals. It is opposite to the previous study which found marriage as an effective factor for early recovery and improved quality of life [18][19][20]. This might be due to the increased marital discords and disharmony between couples which itself now becoming an active factor for relapse this episode The stressful life events has an great impact on functional recovery of patients.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…In this study the marital status is also not showing any significant relation as they also found to be somewhat equal in numbers with more for the married individuals. It is opposite to the previous study which found marriage as an effective factor for early recovery and improved quality of life [18][19][20]. This might be due to the increased marital discords and disharmony between couples which itself now becoming an active factor for relapse this episode The stressful life events has an great impact on functional recovery of patients.…”
Section: Discussioncontrasting
confidence: 52%
“…Among the three scales the depressive patients scored very poor in Subjective wellbeing score with mean= 6 ± 4.2 and range= (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). In other two variables Self-efficacy and the Instrumental activities of daily living scores were fairly well, i.e., mean=23 and 5, respectively.…”
Section: Phases Of Illnessmentioning
confidence: 87%
“…This is consistent with other studies which found that people with epilepsy appear at greater risk of problems in relation to marriage, employment, and socio-economic status. [26][27][28] The present study highlights the impact of epilepsy on the QOL of epileptic patients in Basrah. When compared with the epilepsy-free control group, patients with epilepsy reported a significantly lower QOL across all domains.…”
Section: Discussionmentioning
confidence: 99%
“…Evlilik uyumunun bozulmasýnda genelde eþlerin kiþilik özellikleri, baðlanma özellikleri, aralarýndaki cinsel yaþamýn niteliði, fiziksel ve ruhsal durumlarý ve bazý sosyodemografik özelliklerin etken olduðu araþtýrmalarda belirtilmiþtir (Erberk et al 2005b, Erberk et al 2005a, Gülsün, Ak and Bozkurt 2009. Bipolar hastalar ve eþlerinin evli liðe ve aile iþlevlerine bakýþlarýnýn karþýlaþtýrýldýðý çalýþmalarýn sonuçlarý tutarsýzdýr (Arciszewska, Siwek and Dudek 2015, Granek et al 2016, Targum et al 1981, Vibha et al 2013.…”
Section: Gýrýþunclassified